Rating Of The Adjustments Of The Questıonal Prepoition mI/mU in Turkısh Turkey - Üstüner, Ahat; Yıldırım, Meral (Munzur Üniversitesi, 2024)
In this study, by briefly mentioning the different evaluations and namings in the studies on the preposition mI/mU, which is widely used in Turkey Turkish, the various functions of the preposition, its functions in the sentence, its gradation in adjectives and adverbs are discussed and examined. The use of the mI/mU preposition between repeated adjectives and adverbs with sample sentences selected from Turkey Turkish; In these repetitions, the semantic features it added to the sentence were evaluated with examples taken from various sources.

Bu çalışmada, Türkiye Türkçesinde yaygın olarak kullanılan mI/mU edatı hakkında yapılmış çalışmalarda yer alan farklı değerlendirme ve adlandırmalardan kısaca bahsedilerek, edatın çeşitli görevleri, cümle içindeki işlevleri sıfat ve zarflarda yaptığı derecelendirme ele alınmış ve incelenmiştir. Türkiye Türkçesinden seçilen örnek cümlelerle mI/mU edatının tekrarlanan sıfat ve zarflar arasında kullanılışı; bu tekrarlarda cümleye kattığı anlam özellikleri çeşitli kaynaklardan alınan örneklerle değerlendirilmiştir.
Türkiye Türkçesinde mI/mU Soru Edatının Sıfatları Derecelendirmesi
Keywords: Sociology (Other); Sosyoloji (Diğer)